2019
DOI: 10.1038/s41598-019-44822-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of antiseptic adaptation and cross-adapatation in selected oral pathogens in vitro

Abstract: There is evidence that pathogenic bacteria can adapt to antiseptics upon repeated exposure. More alarming is the concomitant increase in antibiotic resistance that has been described for some pathogens. Unfortunately, effects of adaptation and cross-adaptation are hardly known for oral pathogens, which are very frequently exposed to antiseptics. Therefore, this study aimed to determine the in vitro increase in minimum inhibitory concentrations (MICs) in oral pathogens after repeated expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 51 publications
(66 reference statements)
1
50
0
5
Order By: Relevance
“…Kitagawa et al also examined protein expression profiles of their CHX-adapted E. faecalis strain and its WT strain by SDS-PAGE and found an additional 19-kDa band in the protein expression of the adapted strain [31], which had previously been found in vancomycin-resistant enterococci [66]. Verspecht et al analyzed the proteomes of their adapted and WT strains and found that antiseptic-adapted bacteria changed their metabolic profiles by upregulation of proteins involved in energy metabolism and in amino acid, nucleotide, and inorganic ion metabolisms [32], which has analogously been described for some S. aureus and Enterococcus spp. that were resistant to various clinically relevant antibiotics [67].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Kitagawa et al also examined protein expression profiles of their CHX-adapted E. faecalis strain and its WT strain by SDS-PAGE and found an additional 19-kDa band in the protein expression of the adapted strain [31], which had previously been found in vancomycin-resistant enterococci [66]. Verspecht et al analyzed the proteomes of their adapted and WT strains and found that antiseptic-adapted bacteria changed their metabolic profiles by upregulation of proteins involved in energy metabolism and in amino acid, nucleotide, and inorganic ion metabolisms [32], which has analogously been described for some S. aureus and Enterococcus spp. that were resistant to various clinically relevant antibiotics [67].…”
Section: Discussionmentioning
confidence: 96%
“…Likewise, Wang et al showed a fourfold MIC-increase in E. faecalis and twofold MIC-increases in F. nucleatum, Streptococcus gordonii, and Porphyromonas gingivalis toward CHX upon 10 suchlike passages [63]. Employing a similar methodology, Verspecht et al reported 1.3-to 5.5-fold MIC increases toward CHX and CPC in Aggregatibacter actinomycetemcomitans, F. nucleatum, P. gingivalis, Prevotella intermedia, S. mutans, and Streptococcus sobrinus, depending on the bacterial strain and the tested antiseptic [32]. However, these three studies evaluated phenotypic adaptation by exerting continuous selection pressure due to constant presence of the antiseptic [31,32,63].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transcriptomic (33) and proteomic (10,11,33,34) alterations of QAC adapted strains have been reported but no insights into potential genomic alterations are available.…”
Section: Qacs and Other Antiseptics Lack Clearly Defined Resistance Bmentioning
confidence: 99%